ہندو مصنفین کی کتبِ سیرت میں اسلامی شخصیات کے حوالے سے پیش کردہ تصورات: ایک تحقیقی و تنقیدی مطالعہ : The Perspectives of Hindu Authors on Islamic Personalities in Biographical Literature: A Research and Critical Study - Dr. Muhammad Mumtaz Ul Hasan; Muhammad Pervaiz (International Research Journal of Arabic and Islamic Studies, 2024)
Islamic history and the biography of Prophet Muhammad ﷺ have been a significant area of interest globally, inspiring diverse opinions across religions and cultures. Hindu authors, being an integral part of the South Asian religious and social fabric, have also contributed to this discourse by expressing their perspectives on Islamic personalities and history. This research critically examines the views presented by Hindu authors in their biographical works regarding Islamic figures.The primary aim of this study is to analyze the writings of Hindu authors that focus on Islamic personalities, particularly Prophet Muhammad ﷺ and other key Islamic leaders. It explores how these personalities are portrayed, identifies the prevalence of positive or negative tendencies in their narratives, and evaluates whether their perspectives align with historical realities or are influenced by religious and cultural biases.The research employs historical, comparative, and critical methodologies to review the works of Hindu authors that discuss Islamic biographies or history. The key research questions include.What is the foundation of the praise or criticism found in Hindu authors' narratives about Islamic personalities?Are their perspectives rooted in historical evidence or shaped by personal and religious inclinations?Do these writings promote interfaith harmony or exacerbate religious divides?The findings reveal a diverse portrayal of Islamic personalities in the narratives of Hindu authors. Some writers have acknowledged the moral greatness, human equality, and justice exemplified by Islamic figures, while others have adopted a critical or contentious approach. Several authors have attempted to interpret the events of Prophet Muhammad's ﷺ life through the lens of Hindu philosophy, reflecting their unique cultural contexts.The study concludes that, despite traces of bias in these writings, many contain elements of admiration and appreciation. A critical analysis of these works highlights how these authors’ perspectives are shaped not only by their religious and cultural backgrounds but also by their political and social environments.This study emphasizes the importance of interfaith dialogue and underscores the need for fostering intellectual exchange and understanding between Hindu and Muslim communities. It concludes with the recommendation for further in-depth research on such topics to strengthen harmony between civilizations.